Difunctional Graphene–Fe3O4 Hybrid Nanosheet/Polydimethylsiloxane Nanocomposites with High Positive Piezoresistive and Superparamagnetism Properties as Flexible Touch Sensors. Issue 1 (29th October 2015) - Zha, Jun‐Wei; Huang, Wei; Wang, Si‐Jiao; Zhang, Dong‐Li; Li, Robert K. Y.; Dang, Zhi‐Min
Abstract : Functional materials with excellent electrical and magnetic properties have a potential application in most high‐tech fields. Here, superparamagnetic graphene–Fe3 O4 (G–F) nanosheet hybrids are prepared by a facile one‐step hydrothermal process, which will beneficial to well combine with various polymer matrix to get binary functional composites. Polydimethylsiloxane (PDMS) nanocomposites filled with G–F nanosheets are prepared by a three rolling method. The microstructures of G–F nanosheets as well as the electrical, piezoresistive, and magnetic properties of the G–F/PDMS nanocomposites are investigated. Slightly above the percolation threshold ( f c = 3.4 wt%), the G–F/PDMS nanocomposites with 3.65 wt% of G–F nanosheets show a high conductivity, which is about 10 orders of magnitudes higher than that of pure PDMS, showing an obvious insulator–semiconductor transition. Moreover, the resistance of the nanocomposites with G–F filler near the percolation threshold exponentially increases with the uniaxial pressure. The normalized resistance ( R / R 0 ) can reach up to 870 at 0.88 MPa with 3.65 wt% G–F nanosheets loading. The G–F/PDMS nanocomposites also show superparamagnetism with saturation magnetization values of 0.21 emu g −1 . These results suggest that the G–F/PDMS nanocomposites in this work provide a new route to fabricate difunctional polymer‐based nanocomposites with a potential application as flexible touch sensors. Abstract : A facile one‐step hydrothermal process to prepare superparamagnetic graphene‐Fe3 O4 (G–F) nanosheet hybrids and corresponding difunctional G–F/polydimethylsiloxane (PDMS) nanocomposites with good piezoresistivity and superparamagnetism is developed. The excellent difunctionality of the G–F/PDMS nanocomposites can be attributed to the good interface interaction and the introduction of G–F nanosheets with better dispersibility.